Restoring scratched cine-film via reducing light scattering - Qingmeng Xu; Feifan Xu; Hongjie Luo; Daodao Hu (Heritage Science, 2021)
Abstract Scratches on cine-film significantly affect the quality of projected film images forming blackness or brightness. Only blackness can be restored by restoration dispersion. However, why the scratches can or can not be restored is unknown. Herein, unscratched and scratched films were selected, treated with restoration dispersion and investigated from composition and microstructure and its interaction with light. Both superficial and penetrating scratches make film rough and the applying of restoration dispersion decreases the roughness. The darkness in the projected film image resulted by superficial scratch can be restored by restoration dispersion through reducing light scattering, while the brightness induced by penetrating scratch can not be restored by restoration dispersion due to the removal of emulsion layer. This investigation is beneficial for developing new restoration dispersion to improve the quality of projected film images.